An evaluation of barriers and facilitators to implementing multiplex rapid antigen testing for SARS-CoV-2 and influenza A and B in congregate living settings - Yasmin Garad; Andreea A. Manea; Negin Pak; Lames Danok; Stefan Baral; Stefan Baral; Tom Dykstra; Danielle Kasperavicius; Sharon E. Straus; Sharon E. Straus; Christine Fahim; Christine Fahim (Frontiers in Public Health)
IntroductionPoint of care multiplex rapid antigen testing (RAT) is a tool that can be used to mitigate and respond to facility-based infectious disease outbreaks. However, little is known about how to optimally implement this testing in congregate living settings (CLSs), including long term care homes (LTCHs), retirement homes (RHs), and shelters serving people experiencing homelessness. Our objective was to explore the barriers and facilitators to implementing a new device for multiplex RAT for COVID-19 and influenza across CLSs in the Greater Toronto Area, Canada.Materials and methodsUsing key informant interviews, we assessed barriers and facilitators to implementing multiplex RAT across CLSs. Qualitative coding using the framework approach was used to identify themes. We used the Theoretical Domains Framework (TDF) and the Consolidated Framework for Implementation Research (CFIR) to identify individual and contextual-level barriers and facilitators to implementation. Identified barriers were then mapped to implementation strategies using theoretically-rooted frameworks and tools.ResultsWe completed 45 interviews with staff at CLSs (8 LTCHs, 4 RHs, 12 shelters) between January 2022 and March 2023. Four barriers to RAT implementation in CLSs emerged including: limited material resources for implementation; insufficient staff capacity to perform RAT testing; complexity of RAT implementation; and reluctance among staff to adopt a new testing process. Five facilitators to implementation were described including: training and implementation support for staff at the CLSs; site-level implementation champions; access to materials to support testing; perceived advantages of simultaneous testing for COVID-19 and influenza; and the usability and functionality of the RAT testing device. Twenty implementation strategies were identified through implementation strategy mapping.DiscussionMultiplex RAT options can empower CLS staff to promptly identify and respond to viral respiratory outbreaks. The use of evidence-based implementation strategies can enhance the effectiveness of using multiplex RAT to control outbreaks in CLSs.